Aktivitas ACCase mesokarp kelapa sawit dan kloning fragmen gen penyandi ACCase subunit biotin karboksilase ACCase activity of oil palm mesocarp and cloning of gene fragment encoding biotin carboxylase subunit of ACCase - Asmini BUDIANI; Djoko SANTOSO; Hajrial ASWIDINNOOR; Antonius SUWANTO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2006)
Summary Genetic engineering to produce high yielding oil palm might be done by over expressing gene encoding key enzyme for oil biosynthesis in the oil palm mesocarp, one of which is ACCase. The objective of this research was to analyze ACCase activity of mesocarp from several developmental stages of fruit and to clone conserved region cDNA of gene encoding biotin carboxylase subunit of ACCase (BC-htACCase) from oil palm mesocarp. Activity of ACCase was analyzed by HPLC. Amplification of cDNA was done by means of reverse transcriptase polymerase chain reaction (RT-PCR) using degenerate heterologous primer on several annealing temperature and MgCl2 concentration. The cDNA fragment of RT-PCR product was cloned, sequenced and analyzed to confirm that the cloned cDNA was conserved region of BC-htACCase. The result showed that ACCase activity increased from the 14 week to the 20 week-old fruit, and then decreased. Using heterologous degenerate primers, cDNA fragments of BC-htACCase conserved region (469 bp) can be specifically amplified at 60 oC annealing temperature with 2 mM MgCl2 concentration.The result of BlastX analysis showed that the sequence of cloned cDNA fragment was highly homologous with the conserved region of BC-htACCase from Glycine max, Arabidopsis thaliana, Nicotiana tabacum, and Brassica napus with 243, 237, 236, 231 bit score, and E. value 2e-63, 1e-61, 2e-61 and 5e-60, respectively. Ringkasan Rekayasa genetika untuk menghasilkan bibit kelapa sawit berdaya hasil tinggi dapat ditempuh dengan meningkatkan ekspresi gen penyandi enzim kunci biosintesis minyak pada kelapa sawit, salah satunya adalah ACCase. Tujuan penelitian ini adalah menguji aktivitas ACCase mesokarp beberapa tahap perkem-bangan buah sawit dan mengklon fragmen cDNA daerah konservatif gen penyandi ACCase heteromerik subunit biotin karbok-silase (BC-htACCase) dari mesokarp buah sawit. Aktivitas ACCase dianalisis dengan HPLC. Amplifikasi cDNA dilakukan dengan teknik RT-PCR menggunakan primer degene-rate heterologus pada berbagai suhu penempelan dan konsentrasi MgCl2. Fragmen cDNA hasil RT-PCR diklon, disekuen dan dianalisis untuk mengkonfirmasi bahwa cDNA terklon adalah daerah konservatif BC-htACCase. Hasil penelitian menunjukkan bahwa aktivitas ACCase meningkat dari buah berumur 14 minggu hingga buah berumur 20 minggu, kemudian menurun kembali Dengan primer degenerate heterologus, fragmen cDNA daerah konservatif BC-htACCase (469 pb) dapat diamplifikasi secara spesifik pada suhu penempelan 60 oC dan konsentrasi MgCl2 2 mM. Hasil analisis BlastX dari sekuen DNA fragmen terklon menunjuk-kan bahwa sekuen tersebut mempunyai homologi tinggi antara lain dengan gen penyandi BC-htACCase dari Glycine max, Arabidopsis thaliana, Nicotiana tabacum dan Brassica napus, masing-masing dengan skor 243, 237, 236, 231 bit, dan E. value 2e-63, 1e-61, 2e-61 dan 5e-60.